2020
DOI: 10.1108/cw-02-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of system-on-chip for peripheral component interconnect express encryption card based on multiple algorithms

Abstract: Purpose The data protection is always a vital problem in the network era. High-speed cryptographic chip is an important part to ensure data security in information interaction. This paper aims to provide a new peripheral component interconnect express (PCIe) encryption card solution with high performance, high integration and low cost. Design/methodology/approach This work proposes a System on Chip architecture scheme of high-speed cryptographic chip for PCIe encryption card. It integrated CPU, direct memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Aiming at the problem of high training cost of traditional PS security assessment model, Thams et al proposed an improved and highly scalable algorithm based on complex network theory, and empirically analysed the algorithm, and found that the algorithm's training cost is much lower, and its training time is 10% of that of the traditional algorithm, which is of practical application value 15 . In order to protect PN data security, Chen et al proposed an improved encryption system architecture based on high-speed encryption chip, and empirically tested the scheme, and found that the scheme can meet the performance of most cryptographic operations, with a certain degree of ubiquity, and has the potential for practical application 16 . In order to conduct real-time analysis of complex PS and respond to emergencies, Silva et al proposed and risk response only system based on static security analysis, and empirical analysis of the system found that the system can cut off emergencies, and its response accuracy rate is close to 59%, which is of practical use value 17 .…”
Section: Related Workmentioning
confidence: 99%
“…Aiming at the problem of high training cost of traditional PS security assessment model, Thams et al proposed an improved and highly scalable algorithm based on complex network theory, and empirically analysed the algorithm, and found that the algorithm's training cost is much lower, and its training time is 10% of that of the traditional algorithm, which is of practical application value 15 . In order to protect PN data security, Chen et al proposed an improved encryption system architecture based on high-speed encryption chip, and empirically tested the scheme, and found that the scheme can meet the performance of most cryptographic operations, with a certain degree of ubiquity, and has the potential for practical application 16 . In order to conduct real-time analysis of complex PS and respond to emergencies, Silva et al proposed and risk response only system based on static security analysis, and empirical analysis of the system found that the system can cut off emergencies, and its response accuracy rate is close to 59%, which is of practical use value 17 .…”
Section: Related Workmentioning
confidence: 99%
“…Today's current stage of information technology and computer networks has been able to develop rapidly, and at the same time, it has had a certain impact on contemporary society and, even to a certain extent, has changed the whole world. However, in the whole development process, people should pay attention to the sensitivity and specificity of data and information issues, and at the same time, strengthen the information encryption and protection of the importance of information, and can effectively promote the current computer network communication security [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Peng Peng. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%